Date palm wood waste-based composites for green thermal insulation boards. (November 2021) - Abu-Jdayil, Basim; Barkhad, Mohamed Saeed; Mourad, Abdel-Hamid I.; Iqbal, Muhammad Z.
Abstract: A green polymer composite consisting of date palm wood powder (DPWP) and polylactic acid (PLA) was developed, as an insulating material. DPWP (10–50 wt%) was mixed with PLA in a melt extruder, followed by compression molding and annealing processes. The composites were investigated to evaluate their physical (density, water absorption and degree of crystallization), thermal (thermal conductivity, thermal diffusivity, glass transition and melting temperature) and mechanical properties. Moreover, the structure of the developed composites was characterized by FTIR, XRD and SEM techniques. The characterized properties of the PLA-DPWP composites, displayed that a thermally stable composite material with insulation and construction capacity can be produced by the addition of DPWP to PLA matrix. Addition of DPWP decreased the composite's thermal conductivity to a minimum of 0.0692  W / ( m . K ) at 30 w t . % DPWP contents. In addition, the thermal diffusivity decreased as filler contents were increased, reaching a minimum value of 0.036 m m 2 / s . Although the water absorption was observed to increase with DPWP contents, it showed very low values (less than 2%) compared to the conventional thermal insulation materials. The PLA-DPWP composites demonstrated superior compressive strength compared to commonly used insulating materials, which was comparable to some construction materials. A compressive strength of ∼65 MPa was measured for the composites with 30–50 w t . % filler contents. The results of this work revealed that PLA-DPWP composites have high potential as promising green thermal insulation material owing to their low thermal conductivity, thermal diffusivity, and water absorption while maintaining high mechanical strength. Therefore, recycling of DPWP waste, which is cheap, as filler materials for green thermal insulators, is of significant benefits to both the economy and environment. Graphical abstract: Image 1 Highlights: Green thermal insulation based on date palm wood powder (DPWP) was developed. DPWP was utilized as a filler in PLA based composites. PLA-DPWP composites display superior thermal insulation and construction capacity. Composites show low thermal conductivity (0.0692 W / ( m . K ) ) and diffusivity (0.036 m m 2 / s ) A compressive strength value of ∼65 MPa was measured for the PLA-DPWP composites.